EFEKTIFITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI METODE KOOPERATIF TIPE THINK PAIR SHARE - Siti Suwaibatul Aslamiyah (Universitas Islam Lamongan, 2017)
Teachers have a very important role in educational success. Therefore, teachers are required to work professionally. The professionalism of a teacher can be seen from the competence he has. There are 4 competencies that must be owned by the teacher namely; professional competence, paedagogic competence, personality competence, and social competence. The form of realization of the competent professional teacher is seen from how he did learning in the classroom. A professional teacher in teaching can skillfully use various methods so that the learning process is not boring. One method that can be used by a teacher is the Think Pair Share Co-operative method. Through the method of cooperative learning type think pair share is expected learning outcomes especially Islamic religious education more effective. Think Pair Share type cooperative method can improve students' ability in remembering information and also a student can learn from other students and give each other their idea to be discussed before it is delivered in front of class. In addition, Think Pair Share can also improve confidence and all students are given the opportunity to participate in the class. Here the teacher is no longer the sole source of learning, however, it is precisely the student is required to be able to discover and understand new concepts of the questions asked by the teacher before the material begins.Keywords: PAI Learning, Cooperative Method Think Pair Share Type